Accuracy and feasibility of real - time three dimensional transthoracic echocardiography in valvular pulmonary stenosis pre and post catheterization - Hoda Hussein Barakat; Bahia Hassan Mostafa; Hanan Zekry Khaled; Sahar Shaker Sheta (Cairo : Hoda Hussein Barakat, 2010)
This is a prospective comparative clinical study including 30 patients previously diagnosed to have moderate to severe pulmonary valvular stenosis to compare between the pulmonary valve annulus by 2D echo RT -3D echo versus angiographic catheter calibration in the catherter laboratory before transvalvular balloon angioplasty dilatation
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Congenital heart defect; Echocardiography; Pulmonary stenosis